ANALYSIS OF THE EFFECTIVENESS OF ASN WORK AT THE POPULATION CONTROL AND FAMILY PLANNING OFFICE OF MANDAILING NATAL REGENCY - Santi, Ely; Lubis, Maksum Syahri; Batubara, Beby Masitho (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to analyze the effectiveness of the work of State Civil Apparatus (ASN) at the Population Control and Family Planning Office (KPPKB) of Mandailing Natal Regency. Five main variables were analyzed, namely competence, motivation, job satisfaction, work environment, and management support. A quantitative method with a survey approach was used on 80 ASN respondents, and the data was analyzed using multiple linear regression. The results of the study show that these five variables have a significant effect on work effectiveness, both partially and simultaneously, with management support as the most dominant factor. Managerial support and a conducive work environment play a big role in increasing the effectiveness of ASN's work, while competence, motivation, and job satisfaction also make an important contribution. These findings support the theory that effective performance in the public sector is influenced by a combination of individual and situational factors. This study provides recommendations for KPPKB to strengthen managerial support, improve competence through training, and create a supportive work environment so that the effectiveness of ASN work can be further improved.